The pigman & me - Zindel, Paul. (New York : HarperCollins, 1992)
An account of Paul Zindel's teenage years on Staten Island, when his life was enriched by finding his own personal pigman, or mentor.
"A Charlotte Zolotow book".
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
6.7
7-9
Keywords: Zindel, Paul -- Childhood and youth -- Juvenile literature; Zindel, Paul -- Childhood and youth; Zindel, Paul; Authors, American -- 20th century -- Biography -- Juvenile literature; Authors, American; American authors -- Biography; Staten Island (New York, N.Y.) -- Social life and customs -- Juvenile literature